GED test for dummies - Shukyn, Murray; Shuttleworth, Dale E. (Dale Edwin) 1938-; Krull, Achim K. (Hoboken, New Jersey John Wiley & Sons Inc., 2015)
Presents subject review, full-length practice tests with answer explanations, and test-taking strategies to help readers prepare for and score higher on the high school equivalency test.
Part I: Getting started with the GED test -- Part II: Minding your Ps and Qs: The reasoning through language arts test -- Part III: Finding your way: The social studies test -- Part IV: Peering at your specimen: The science test -- Part V: Counting all the possible solutions: The mathematical reasoning test -- Part VI: Putting your skills to the test: GED practice test 1-- Part VII: Getting more test practice: GED practice test 2 -- Part VIII: The part of tens.
Includes index.
If you're preparing for this important exam, GED Test For Dummies, 3rd Edition gets you up and running on everything you can expect on test day, from overviews of the test sections to invaluable reviews and test-taking strategies for all the subjects covered -- and everything in between.
Keywords: GED tests -- Study guides; High school equivalency examinations -- Study guides